2019
DOI: 10.1111/icad.12376
|View full text |Cite
|
Sign up to set email alerts
|

The role of climate and biotic factors in shaping current distributions and potential future shifts of EuropeanNeocrepidodera(Coleoptera, Chrysomelidae)

Abstract: 1. The Western Paleartic species of Neocrepidodera Heikertinger (Coleoptera: Chrysomelidae: Galerucinae: Alticini) mostly occur in medium and high elevation ecosystems particularly sensitive to climate change. 2. Here, using ensemble projections from state-of-the-art habitat suitability modelling techniques, we investigated how climate change and associated changes in host availability may affect the persistence of three pairs of closely related Neocrepidodera taxa. 3. Modelled niches and suitability patterns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 66 publications
1
13
0
Order By: Relevance
“…This result is in line with other published trends, in which low temperatures are important in determining the distribution of insects with some invasive alien insects favoured by an increase in the low temperatures that are likely to occur with global warming in the future (Orlova-Bienkowskaja & Bienkowski, 2016;Iannella et al, 2019b). In marked contrast, high altitude and endemic species are not favoured by the predicted temperature increase (Urbani et al, 2017;Brunetti et al, 2019;Cerasoli et al, 2020). Depending on the climatic scenario and RCP used, an increase in BIO11 is observable from south-western to north-eastern Europe, which is very similar and concurrent with the future predictions (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…This result is in line with other published trends, in which low temperatures are important in determining the distribution of insects with some invasive alien insects favoured by an increase in the low temperatures that are likely to occur with global warming in the future (Orlova-Bienkowskaja & Bienkowski, 2016;Iannella et al, 2019b). In marked contrast, high altitude and endemic species are not favoured by the predicted temperature increase (Urbani et al, 2017;Brunetti et al, 2019;Cerasoli et al, 2020). Depending on the climatic scenario and RCP used, an increase in BIO11 is observable from south-western to north-eastern Europe, which is very similar and concurrent with the future predictions (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…The α-convex hull is ultimately defined by the parameter α, which affects the entire shape of the output [60]. Alpha was chosen in advance and set to three different values reflecting a varying extent of stringency according to the literature (for example [64,[66][67][68][69][70][71][72][73][74][75]. The most conservative approach (later referred to as 'approach A') in choosing α, encompassing the least area, was calculated with α = 0.8, as this value was at the verge of producing complete hulls rather than a mesh between observations.…”
Section: Spatial Estimationsmentioning
confidence: 99%
“…The most conservative approach (later referred to as 'approach A') in choosing α, encompassing the least area, was calculated with α = 0.8, as this value was at the verge of producing complete hulls rather than a mesh between observations. For the radical approach (later referred to as 'approach C') we set α = 1.8, because it was the smallest value resulting in one shared hull approximately including all data points to avoid a disjunct distribution and, consequentially, encompassed the largest area of the α convex hull reconstruction [64,67,69]. As intermediate approach (later referred to as 'approach B'), we chose an average value of α = 1.3.…”
Section: Spatial Estimationsmentioning
confidence: 99%
“…Although previous modelling studies have also found temperature seasonality to be an important variable in the structuring of species' distributions (e.g. Barbet-Massin & Jetz, 2014;Cerasoli et al, 2020;Zhang et al, 2018), this result was somewhat unexpected. VanDerWal et al (2009) suggests that variable importance can become increasingly dominated by a small number of variables as the PA selection extent increases.…”
Section: Trends In Sdm Outputsmentioning
confidence: 52%